The Dialectics of Polygamy in the Matrilineal System of 20th Century Minangkabau - Armi, Mhd. Ilham; Azhari, Susiknan (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
This study is motivated by the massive phenomenon of polygamy in Minangkabau during the 1920s and 1930s, which was recorded as the highest prevalence in the archipelago. The main issue discussed is the dynamics of the transformation of marriage customs and family structures resulting from the dialectic among three local elite groups. These three elites include: the customs elite, which maintained polygamy as a means of social prestige and the distribution of ancestral property (pusako); the religious elite, which provided theological legitimacy through Islamic law; and the modern elite, which advocated monogamy based on the principles of gender equality and modern rationality. This issue is analyzed using a literature review method with a thematic and socio-legal approach to various historical documents and 20th-century media publications. This study reveals how each elite group renegotiated its legitimacy in the public sphere in response to social disruption caused by colonialism and modernization. The results of the study show that polygamy was initially strongly cohesive within the matrilineal system to maintain social status. However, critical reflections from the modern elite, especially through the women’s education movement and media publications in the first half of the 20th century, triggered a paradigm shift towards family independence. This dialectic transformed the Minangkabau family structure into two objective realities: a matrilocal-polygamous pattern grounded in customary communalism, and a neolocal-monogamous pattern emphasizing the autonomy of the nuclear family. This transformation resulted in an ideal marriage pattern that integrated customs, Islam, and modernity to achieve more inclusive benefits for women. The neolocal structure ultimately redefined the role of the husband as the fully responsible head of the family, while mitigating the risk of systemic injustice that was previously inherent in customary polygamy practices. [Kajian ini dilatarbelakangi oleh fenomena masifnya praktik poligami di Minangkabau pada periode 1920-1930-an yang tercatat sebagai prevalensi tertinggi di Nusantara. Masalah utama yang dibahas adalah dinamika transformasi adat perkawinan dan struktur keluarga akibat dialektika yang melibatkan tiga kelompok elite lokal. Ketiga elite tersebut mencakup: elite adat yang mempertahankan poligami sebagai sarana prestise sosial dan distribusi harta warisan adat (pusako); elite agama yang memberikan legitimasi teologis melalui syariat Islam; serta elite modern yang mengadvokasi monogami berdasarkan prinsip kesetaraan gender dan rasionalitas modern. Permasalahan ini dianalisis menggunakan metode kepustakaan dengan pendekatan sejarah tematik dan sosio-legal terhadap berbagai dokumentasi sejarah serta publikasi media abad ke-20. Kajian ini mengungkap bagaimana setiap kelompok elite menegosiasikan ulang legitimasinya dalam ruang publik guna merespons disrupsi sosial akibat kolonialisme dan modernisasi. Hasil kajian menunjukkan bahwa poligami pada awalnya berkohesi kuat dalam sistem matrilineal untuk menjaga status sosial. Namun, refleksi kritis dari elite modern, terutama melalui gerakan pendidikan perempuan dan publikasi media paruh pertama abad ke-20, memicu pergeseran paradigma menuju kemandirian keluarga. Dialektika ini mentransformasi struktur keluarga Minangkabau menjadi dua realitas objektif: pola poligami-matrilokal yang berbasis pada komunalitas adat, dan pola monogami-neolokal yang menekankan otonomi keluarga inti. Transformasi tersebut menghasilkan pola perkawinan ideal yang mengintegrasikan nilai adat, Islam, dan modernitas guna mewujudkan kemaslahatan yang lebih inklusif bagi perempuan. Struktur neolokal pada akhirnya meredefinisikan peran suami sebagai kepala keluarga yang bertanggung jawab penuh, dengan memitigasi risiko ketidakadilan sistemik yang sebelumnya melekat pada praktik poligami adat.]